Bridging Literature and Linguistics - Abdul Wahab (TEFLIN, 2003)
Two majors linguistics and literature in the schools of letters both in the state and private universities throughout Indonesia are commonly separated sharply. Courses of literature in the Department of Linguistics are offered minimally, such that the students of linguistics are not given a conducive atmosphere to express their literary appreciation. Likewise, courses of linguistics in the Department of Literature are very restricted, so that the students of literature are unable to analyze literary works from the points of linguistic view. This paper tries to bridge linguistics and literature. The attempt to bridge linguistics and literature is based on three postulates: (1) literature consists of linguistic objects designed with an artistic end, (2) linguistic objects are formal objects, and (3) a formal account of linguistic object designed with an artistic end approximates a formal account of that artistic design. Two major directions in the approaches and emphases will be presented in the paper exogenous and endogenous. Exogenous approach tries to search for adequate description of (1) poetic language as contrasted with ordinary language, (2) language of a particular author contrasted with that of other authors, and (3) a particular literary work contrasted with other works of the same author. This part touches upon three areas of exogenous approach isolation, description, and characterization. Endogenous, on the hand, is based upon an assumption that a writer exhibits, probably without realizing it, certain systematic preferences for particular aspects of linguistic patterns. Planning a bridge between linguistics and literature is by no means without problems. Therefore, this paper also presents some possible solutions.